Stereoselective Total Syntheses of Paecilomycins E and F through a Protecting Group Directed Diastereoselective Intermolecular Nozaki–Hiyama–Kishi (NHK) Reaction. Issue 23 (11th July 2014) - Mohapatra, Debendra K.; Reddy, D. Sai; Mallampudi, N. Arjunreddy; Yadav, Jhillu S.
Abstract: An efficient and concise approach to the total syntheses of paecilomycins E (1 ) and F (2 ) is described. A protecting group directed intermolecular diastereoselective Nozaki–Hiyama–Kishi (NHK) reaction, a Julia–Kocienski olefination, a Sharpless asymmetric dihydroxylation, and De Brabander's lactonization protocol are used as the key steps. Abstract : The convergent and concise total syntheses of paecilomycins E and F were achieved through 10 linear steps in high overall yields from known intermediates. A protecting group directed diastereoselective intermolecular Nozaki–Hiyama–Kishi (NHK) reaction, a Julia–Kocienski olefination, a Sharpless asymmetric dihydroxylation, and De Brabander's lactonization protocol were employed as the key steps.